Measurements of triple-differential cross sections for inclusive isolated-photon plus jet events in pp collisions at root s=8 TeV - (:unkn) unknown (SPRINGER, 2019)
Measurements are presented of the triple-differential cross section for inclusive isolated-photon+jet events in pp collisions at root s = 8 TeV as a function of photon transverse momentum (p(T)(gamma)), photon pseudorapidity (eta(gamma)), and jet pseudorapidity (eta(jet)). The data correspond to an integrated luminosity of 19.7 fb(-1) that probe a broad range of the available phase space, for vertical bar eta(gamma)vertical bar < 1.44 and 1.57 < vertical bar eta(gamma)vertical bar < 2.50, vertical bar eta(jet)vertical bar < 2.5, 40 < p(T)(gamma) < 1000 GeV, and jet transverse momentum, p(T)(jet), > 25 GeV. The measurements are compared to next-to-leading order perturbative quantum chromodynamics calculations, which reproduce the data within uncertainties.